AKUPRESUR TITIK ST 16 DAN ST 18 MENINGKATKAN PRODUKSI ASI PADA IBU POST SECTIO CESAREAN: SEBUAH STUDI QUASI-EKSPERIMENTAL - Setiawandari Setiawandari; Wiwin Windiati (Rena Cipta Mandiri, 2026)
Post-cesarean section mothers often experience delayed and insufficient breast milk production due to pain, anxiety, and limited mobility, so that the breastfeeding process in the first days is not optimal. Nationally, the rate of delivery via cesarean section reaches 17.6%, and in East Java it is 19.1%, with a lower rate of early breastfeeding success compared to normal delivery. Acupressure is a complementary approach that is easy to do and inexpensive to help the mother's body relax, increase blood flow to the breast area, and stimulate the release of prolactin and oxytocin hormones that play an important role in breast milk production. The purpose of this study was to analyze the effect of acupressure on ST 16 and ST 18 points on breast milk production after CS. The research method was quasi-experimental with a one-group pretest–posttest design on 26 post-CS mothers on day 2. The results of the Wilcoxon Signed Rank-Test p-value = 0.000 indicating a significant difference between breast milk production before and after acupressure. The conclusion is that there is an effect of acupressure on the ST 16 and ST 18 points on breast milk production after a caesarean section, with a difference in the increase in breast milk production of 161.35 cc.